PERANCANGAN ULANG UI/UX DESAIN WEBSITE AESIA DENGAN METODE DESIGN THINKING - Wibisono, Yusuf Akbar (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The State Asset Management Agency (LMAN) has the purpose and function of providing asset management services (especially property) to the public, both government, private, and the wider community in a fast, precise, optimal, and accountable manner. This service is accessed through the LMAN website called AESIA (property solution). Along with the rapid development of technology, LMAN always strives for optimal service through its website. For this reason, LMAN conducts UI/UX re-design on the website as a form of optimizing information services regarding asset management to the public. The UI/UX redesign of the AESIA LMAN website aims to identify user needs so as to produce a website that is simpler, informative, flexible, and easily accessible by users. Then designed using the Design Thinking method, involving the empathy, define, ideate, prototype, and testing stages. The results of the UI/UX redesign testing will show the suitability of AESIA's website user needs. With the results of this test, it can be concluded that the redesign of the UI/UX design of the AESIA website successfully meets the needs of users based on the criteria that have been submitted by users. This confirms that the redesigned UI/UX design of the AESIA website can be used well, understood, and accessed easily by users.